Peningkatan Daya Saing Melalui Brand Loyalty Pada Persaingan Larutan Penyegar di Jakarta - Saputra Wijaya, Adam; Sutrisno, Nuno (Media Bisnis, 2024)
The purpose of this study is to analyze and test whether factors such as brand image, brand impact, brand value, and brand satisfaction can affect brand loyalty  of Larutan Panas Dalam Cap Badak customers in DKI Jakarta. This research design uses descriptive and causality research, measuring each variable using a 5 point Likert scale. This research uses primary and secondary data and collects data through questionnaires. The research sample was obtained through a purposive sampling method and 110 respondents were obtained.  Data analysis was carried out using multiple linear regression with IBM SPSS 25 statistical test tools. The findings show that brand image, brand impact, brand value and brand satisfaction have an effect on brand loyalty to Larutan Panas Dalam Cap Badak customers in DKI Jakarta. This research is intended to provide guidance or input for companies that specialize in pharmaceuticals, specifically PT Sinde Budi Sentosa or Cap Badak, the focus of this research is to enhance the competitiveness of these companies in the pharmaceutical industry of Indonesia.